Assessing the prognostic value of KRAS mutation combined with tumor size in stage I-II non-small cell lung cancer: a retrospective analysis - Eklund, Ella A.; Mourad, Ali; Wiel, Clotilde; Sayin, Sama I.; Fagman, Henrik; Hallqvist, Andreas; Sayin, Volkan I. (Frontiers in Oncology, 2024)
Background: KRAS mutation status is a well-established independent prognostic factor in advanced non-small cell lung cancer (NSCLC), yet its role in early-stage disease is unclear. Here, we investigate the prognostic value of combining survival data on KRAS mutation status and tumor size in stage I-II NSCLC. Methods: We studied the combined impact of KRAS mutational status and tumor size on overall survival (OS) in patients with stage I-II NSCLC. We performed a retrospective study including 310 diagnosed patients with early (stage I-II) NSCLCs. All molecularly assessed patients diagnosed with stage I-II NSCLC between 2016-2018 in the Västra Götaland Region of western Sweden were screened in this multi-center retrospective study. The primary study outcome was overall survival. Results: Out of 310 patients with stage I-II NSCLC, 37% harbored an activating mutation in the KRAS gene. Our study confirmed staging and tumor size as prognostic factors. However, KRAS mutational status was not found to impact OS and there was no difference in the risk of death when combining KRAS mutational status and primary tumor size. Conclusions: In our patient cohort, KRAS mutations in combination with primary tumor size did not impact prognosis in stage I-II NSCLC.